2021
DOI: 10.3389/fncel.2021.580717
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus Type 1 Neuronal Infection Triggers the Disassembly of Key Structural Components of Dendritic Spines

Abstract: Herpes simplex virus type 1 (HSV-1) is a widespread neurotropic virus. Primary infection of HSV-1 in facial epithelium leads to retrograde axonal transport to the central nervous system (CNS) where it establishes latency. Under stressful conditions, the virus reactivates, and new progeny are transported anterogradely to the primary site of infection. During the late stages of neuronal infection, axonal damage can occur, however, the impact of HSV-1 infection on the morphology and functional integrity of neuron… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…Previous reports showed that lytic HSV-1 neuronal infection caused synaptic dysfunction and disassembly of dendritic spines and upregulation of activity-regulated cytoskeleton-associated protein 25,26 . In our system, we observed massive downregulation of synaptic transmission genes (Extended Data Fig.…”
Section: Hsv-1 Disrupts Neuronal Integrity and Functionalitymentioning
confidence: 95%
“…Previous reports showed that lytic HSV-1 neuronal infection caused synaptic dysfunction and disassembly of dendritic spines and upregulation of activity-regulated cytoskeleton-associated protein 25,26 . In our system, we observed massive downregulation of synaptic transmission genes (Extended Data Fig.…”
Section: Hsv-1 Disrupts Neuronal Integrity and Functionalitymentioning
confidence: 95%
“…The primary infection of HSVs occurs through direct contact of the host mucosal membranes or damaged skin with infected fluids. This virus can then reach and infect sensory neurons, leading to secondary encephalitis ( Bradshaw and Venkatesan, 2016 ; Marcocci et al, 2020 ; Acuña-Hinrichsen et al, 2021 ). The clinical signs described in patients with HSV encephalitis (HSE) are fever, headache, seizure, focal neurological deficits, and general encephalopathy ( Table 1 ; Bradshaw and Venkatesan, 2016 ).…”
Section: Viruses Inducing Encephalitis and Their Impact On The Blood-brain Barriermentioning
confidence: 99%
“…Interestingly, HSV not only infects neurons but can also establish latency on these cells as well as in astrocytes ( Marcocci et al, 2020 ; Słońska et al, 2021 ). HSV-1-infected cortical neurons exhibit an altered expression of dendritic spine proteins as well as their distribution and changes in response to a glutamate stimulation altering the normal function of these cells ( Acuña-Hinrichsen et al, 2021 ). Importantly, HSV-1-infected NCSs present impairment in their growth, proliferation, and neuronal differentiation, which can cause neurodevelopment disorder observed in neonatal HSV-1 infections ( Qiao et al, 2020 ).…”
Section: Immune Response At the Central Nervous System During Viral Infectionsmentioning
confidence: 99%
“…Recently, it was shown that the HSV-1 infection of mice causes hippocampal damage and neuronal apoptosis, which is related to the downregulation of the suppressor of cytokine signaling 2 (SOCS2) and SOCS3, and to increased hippocampal expression of inflammatory cytokines, such as TNFα, IL-1β, IL-6, and IFN-α/β [ 230 ]. In the cultured neurons, HSV-1 infection decreased the expression of the dendritic postsynaptic density scaffolding proteins, such as postsynaptic density protein 95 (PSD-95), Drebrin, and CaMKIIb, and induced extensive loss of dendritic spines and retraction of secondary dendrites, as well as entailed unresponsiveness to glutamate stimulation, culminating in the functional deregulation of neurons [ 231 ]. Latterly, Doll et al provided evidence that sensory neurons undergo apoptosis as a result of HSV reactivation in mice [ 232 ].…”
Section: Apoptosis and Autophagymentioning
confidence: 99%
“…Oligodendrocytes produce exosomes with regulatory RNA and can send functional molecules to neurons, affecting their properties [ 296 ]. HSV-1 influences neuronal physiology, and induces structural disassembly and functional deregulation, as shown in the blue box [ 231 ]. Infected neurons largely secrete IFN-α, IFN-β, IL-1β, CXCL10, and Aβ peptides [ 49 , 84 , 85 , 297 ].…”
Section: Figurementioning
confidence: 99%